Unity Virtual Reality Projects : Learn Virtual Reality by developing more than 10 engaging projects with Unity 2018, 2nd Edition. - Linowes, Jonathan (Packt Publishing, 2018)
If you are interested in Virtual Reality, want to learn how it works, and want to create your own VR experiences, this book is for you. We walk you through a series of tutorials and in-depth discussions using the Unity game engine.